Positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electronic device

Through the positive electrode material doped by specific elements, the problem of dissolving and structural changes in lithium manganate positive materials at high temperatures achieve higher stability and cycle life, and improves the high temperature cycle performance of secondary batteries.

CN119381441AActive Publication Date: 2025-01-28NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202411479710.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-28
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Lithium manganate positive electrode material is prone to dissolution and structural changes in high-temperature environments, resulting in the deterioration of the high-temperature performance and rapid capacity decay of the secondary battery.

Method used

M2 elements such as M1 elements, 镧 elements, 铈 elements such as 、 elements, 铌 elements, or 钽 elements, as well as X element of fluorine, chlorine elements, etc., to prepare a near -spherical two -time particle positive pole material. This material can regulate the content of doping elements in different areas, inhibit the dissolution and structural changes of manganese ions, and improve high temperature circulation performance.

Benefits of technology

Effectively suppress the solubility of manganese in high temperature environments, improve the stability and cycle life of the positive pole materials, and improve the high temperature cycle performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098398300000201
    Figure BDA0005098398300000201
  • Figure BDA0005098398300000211
    Figure BDA0005098398300000211
  • Figure BDA0005098398300000221
    Figure BDA0005098398300000221
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electronic device. The positive electrode material comprises an element M1, an element M2 and an element X; the M1 element comprises one or more of a vanadium element, a niobium element or a tantalum element; m2 element comprises one or more of lanthanum element, cerium element, praseodymium element, samarium element, dysprosium element, ytterbium element, yttrium element or lutetium element; the X element comprises one or more of fluorine element, chlorine element, sulfur element, nitrogen element or boron element. The high-temperature cycle performance can be improved, and the cycle life can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electronic device. Background Art

[0002] In recent years, the application of secondary batteries has become increasingly widespread and diverse, placing higher demands on their performance at unconventional temperatures. Secondary batteries using lithium manganese oxide as the positive electrode material have the advantages of high energy density and low cost. However, under high-temperature conditions, lithium manganese oxide positive electrode materials are prone to dissolution and structural and chemical changes during cyclic charge and discharge, resulting in deterioration of the battery's high-temperature performance and rapid capacity decay. Therefore, there is an urgent need to improve the high-temperature performance of lithium manganese oxide positive electrode batteries. Summary of the Invention

[0003] The embodiments of the present application provide a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electronic device, which can improve the high-temperature cycle performance of a lithium manganese oxide battery.

[0004] In a first aspect, an embodiment of the present application provides a positive electrode material. The positive electrode material includes an M1 element, an M2 element, and an X element; the M1 element includes one or more of vanadium, niobium, or tantalum, and the ratio of the molar amount of the M1 element to the molar amount of the positive electrode material is a; the M2 element includes one or more of lanthanum, cerium, praseodymium, samarium, dysprosium, ytterbium, yttrium, or lutetium, and the ratio of the molar amount of the M2 element to the molar amount of the positive electrode material is b; the X element includes one or more of fluorine, chlorine, sulfur, nitrogen, or boron, and X The ratio of the molar amount of the element to the molar amount of the positive electrode material is c; the above-mentioned positive electrode material is a nearly spherical secondary particle, and the area of ​​the secondary particle from the outer surface along the radial direction to the depth of 100 nm is assumed to be region I, and the area from the center of the sphere along the radial direction to the depth of 100 nm is assumed to be region II; in the above-mentioned region I, 0.02≤a≤0.05, 0.02≤b≤0.05, 0.001≤c≤0.04; in the above-mentioned region II, 0.001≤a≤0.02, 0.001≤b≤0.02.

[0005] Based on the positive electrode materials of the embodiments of the present application, the inventors found that on the basis of lithium manganate as the positive electrode active material, M1 elements including vanadium, niobium or tantalum, M2 elements including lanthanum, cerium, praseodymium, samarium, dysprosium, ytterbium, yttrium or lutetium, and X elements including fluorine, chlorine, sulfur, nitrogen or boron are further doped. By regulating the type and content of the above-mentioned element doping to adjust the grain morphology of the positive electrode material, on the one hand, the (111) crystal plane with a relatively low manganese ion solubility rate in the grain can be highly exposed, thereby inhibiting the manganese dissolution phenomenon in a high temperature environment and improving the high temperature cycle performance; on the other hand, the material structure can be stabilized, the Jan-Taylor effect can be inhibited, and the configuration deformation during long-term cycling can be alleviated, thereby increasing the positive electrode stability and improving the cycle life.

[0006] In some embodiments, in region I, 0.025≤a≤0.045, 0.025≤b≤0.045, 0.005≤c≤0.03; and / or, in region II, 0.005≤a≤0.01, 0.005≤b≤0.01. Based on the above embodiments, the present application further regulates the molar content of elements in regions I and II of the positive electrode material within the above ranges to further suppress manganese dissolution in high-temperature environments, improve high-temperature cycle performance, increase positive electrode stability, and extend cycle life.

[0007] In some embodiments, the positive electrode material includes lithium, and the ratio of the molar amount of lithium to the molar amount of the positive electrode material is d, 1≤d≤1.08. Based on the above embodiments, the present application further regulates the molar concentration of the active material elements in the positive electrode material within an appropriate range to better inhibit manganese dissolution in high-temperature environments, increase positive electrode stability, further improve high-temperature cycle performance, and increase cycle life.

[0008] In some embodiments, the positive electrode material in the above-mentioned region I satisfies at least one of the following conditions: (1) 0.05≤a+b+c≤0.1; (2) 0.001≤c / d≤0.03. Based on the above embodiments, the present application further regulates the molar concentration of the doping elements in the positive electrode material within an appropriate range, so that it can better exert a synergistic effect, better inhibit manganese dissolution in a high-temperature environment, increase the positive electrode stability, further improve the high-temperature cycle performance, and increase the cycle life.

[0009] In some embodiments, the X element is selected from fluorine and / or boron. Based on the above embodiments, the present application can more effectively reduce manganese dissolution in high-temperature environments by selecting the above elements as doping elements, enhance the structural stability of the material, and thus further improve high-temperature cycle performance and increase cycle life.

[0010] In some embodiments, the specific surface area of ​​the positive electrode material is 1 m 2 / g, 0.3≤I≤1.0; and / or, the unit cell parameters of the above-mentioned positive electrode material are 8.2100≤J≤8.2400; and / or, the Dv50 of the above-mentioned positive electrode material is Kμm, 5≤K≤20. Based on the above embodiments, the present application can further improve the high-temperature performance of the material by controlling the specific surface area within the above-mentioned range; further improve the cycling performance of the material by controlling the unit cell parameters within the above-mentioned range; and improve the volumetric energy density of the material by controlling the Dv50 within the above-mentioned range. By synergistically regulating the above-mentioned parameters, they can synergistically further improve the high-temperature cycling performance and increase the cycle life.

[0011] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps: (1) preparing a precursor containing an M1 element and an M2 element; (2) mixing the precursor containing the M1 element and the M2 element, a lithium source, and a manganese source to obtain a precursor A; (3) placing the precursor A in an oxygen-containing atmosphere for a first sintering to obtain a first sintered product as a precursor B; or, placing the precursor A in an oxygen-containing atmosphere for a first sintering to obtain a first sintered product, and then mixing the first sintered product with a precursor containing an X element to obtain a precursor B; (4) placing the precursor B in an oxygen-containing atmosphere for a second sintering to obtain a positive electrode material;

[0012] Wherein, the temperature of the first sintering in step (3) is 450°C to 650°C, and the time is 4h to 8h; the temperature of the second sintering in step (4) is 700°C to 900°C, and the time is 8h to 12h. The lithium source is lithium carbonate and / or lithium hydroxide, and the manganese source is manganese dioxide and / or manganese tetraoxide. Based on the above embodiment, the present application can reduce the defects of the positive electrode material crystals during the generation process through the above preparation steps, and can also control the element distribution inside the positive electrode material to form a core-shell structure material with different doping element concentrations in region I and region II, further improving the high temperature cycle performance and increasing the cycle life.

[0013] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector; the positive electrode material layer comprises the positive electrode material or the positive electrode material prepared by the above method.

[0014] In some embodiments, the positive electrode material layer further includes a ternary lithium material and / or lithium iron manganese phosphate and / or lithium iron phosphate. Based on the above embodiments, by mixing and doping the positive electrode material described in this application with a ternary lithium material and lithium iron manganese phosphate and lithium iron phosphate materials, the ternary material, lithium iron manganese phosphate material and lithium iron phosphate material can achieve a high lithium ion diffusion rate, reduce the contact between the lithium manganese oxide material and the electrolyte, reduce interface side reactions, inhibit the structural degradation of lithium manganese oxide, and protect the lithium manganese oxide material, thereby improving high-temperature cycle performance and increasing cycle life; at the same time, the mixed doping can also make the spinel lithium manganese oxide material have a more stable structure, improve the diffusion impedance of the positive electrode plate under different SOCs, and improve low-temperature performance and safety performance.

[0015] In some embodiments, based on the total mass of the metal elements other than lithium in the positive electrode material layer, the mass percentage of the M1 element is P%, and the mass percentage of the M2 element is Q%, 0.1≤P≤0.5, 0.1≤Q≤0.5. Based on the above embodiments, the present application regulates the ratio of the lithium manganese oxide material to the ternary lithium material and the lithium iron manganese phosphate material in the positive electrode material within an appropriate range so that they can better exert synergistic effects, further improve high-temperature cycle performance, increase cycle life, and take into account improvements in low-temperature performance and safety performance.

[0016] In a fourth aspect, an embodiment of the present application provides a secondary battery comprising the above-mentioned positive electrode plate.

[0017] In a fifth aspect, an embodiment of the present application provides an electronic device comprising the aforementioned secondary battery. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solutions and advantages of this application more clear, the following further describes this application in detail with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.

[0019] An embodiment of the present application provides a secondary battery, including a positive electrode, a non-aqueous electrolyte, a negative electrode, and a separator.

[0020] positive electrode

[0021] <Cathode Material>

[0022] One embodiment of the present application provides a lithium manganate-doped positive electrode material. The positive electrode material includes an M1 element, an M2 element, and an X element. The M1 element includes one or more of vanadium, niobium, or tantalum, and the ratio of the molar amount of the M1 element to the molar amount of the positive electrode material is a. The M2 element includes one or more of lanthanum, cerium, praseodymium, samarium, dysprosium, ytterbium, yttrium, or lutetium, and the ratio of the molar amount of the M2 element to the molar amount of the positive electrode material is b. The X element includes one or more of fluorine, chlorine, sulfur, nitrogen, or boron, and the ratio of the molar amount of the X element to the molar amount of the positive electrode material is c. The positive electrode material is a nearly spherical secondary particle. The region from the outer surface of the secondary particle to a depth of 100 nm is region I, and the region from the center of the sphere to a depth of 100 nm is region II. In region I, 0.02≤a≤0.05, 0.02≤b≤0.05, and 0.001≤c≤0.04. Preferably, in region I, 0.025≤a≤0.045, 0.025≤b≤0.045, and 0.005≤c≤0.03. For example, the value of a in region I can be 0.02, 0.028, 0.037, 0.041, 0.046, 0.05, or a range consisting of any two of these values; for example, the value of b in region I can be 0.02, 0.025, 0.031, 0.042, 0.047, 0.05, or a range consisting of any two of these values; for example, the value of c in region I can be 0.001, 0.005, 0.02, 0.03, 0.04, or a range consisting of any two of these values. In the aforementioned region II, 0.001≤a≤0.02 and 0.001≤b≤0.02 are present. Preferably, in the II region, 0.005≤a≤0.01, 0.005≤b≤0.01. For example, the value of a in the II region may be 0.001, 0.009, 0.012, 0.017, 0.019, 0.02, or a value within the range of any two of these values; for example, the value of b in the II region may be 0.001, 0.004, 0.008, 0.011, 0.016, 0.02, or a value within the range of any two of these values. For example, the positive electrode material may be Li 1.05 Mn 1.88 Nb 0.03 Ce 0.04 O 3.98 F 0.02 , Li 1.055 Mn 1.86 V 0.04 La 0.045 O 3.97 B 0.03 or Li 1.06 Mn 1.855 Ta 0.045 Ce0.04 O 3.985 N 0.015 Based on the positive electrode material of the embodiment of the present application, lithium manganate is used as the positive electrode active material, and further doped with a doping element M1 including vanadium, niobium or tantalum, a doping element M2 including lanthanum, cerium, praseodymium, samarium, dysprosium, ytterbium, yttrium or lutetium, and a doping element X including fluorine, chlorine, sulfur, nitrogen or boron, to inhibit manganese dissolution in a high-temperature environment, thereby increasing the positive electrode stability, improving high-temperature cycle performance, and increasing the cycle life.

[0023] In some embodiments, the positive electrode material includes lithium element, and the ratio of the molar amount of lithium element to the molar amount of positive electrode material is d, 1≤d≤1.08. For example, the value of the ratio d of the molar amount of lithium element to the molar amount of positive electrode material can be 1, 1.01, 1.04, 1.06, 1.07, 1.08 or a value within the range composed of any two of these values. Based on the above embodiments, the present application further regulates the molar concentration of the active material elements in the positive electrode material within a suitable range to better inhibit manganese dissolution in a high temperature environment, increase the stability of the positive electrode, further improve the high temperature cycle performance, and improve the cycle life.

[0024] In some embodiments, the positive electrode material in region I satisfies at least one of the following conditions: (1) 0.05≤a+b+c≤0.1; (2) 0.001≤c / d≤0.03. For example, in region I of the positive electrode material, the value of a+b+c can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a value within the range of any two of these values. For example, in region I of the positive electrode material, the value of c / d can be 0.001, 0.005, 0.01, 0.02, 0.03, or a value within the range of any two of these values. Based on the above embodiments, the present application further regulates the molar concentration of the doping elements in the positive electrode material within a suitable range, so that it can better exert a synergistic effect, better inhibit manganese dissolution in a high temperature environment, increase the stability of the positive electrode, further improve the high temperature cycle performance, and improve the cycle life.

[0025] In some embodiments, the X element is selected from fluorine and / or boron. For example, the X element is fluorine and boron. Based on the above embodiments, the present application further improves high-temperature cycling performance and cycle life by selecting the above elements as doping elements.

[0026] In some embodiments, the specific surface area of ​​the positive electrode material is 1 m 2 / g, 0.3≤I≤1.0. For example, the specific surface area I of the positive electrode material can be 0.3, 0.4, 0.6, 0.7, 0.9, 1.0 or a value within the range of any two of these values. The unit cell parameter of the positive electrode material is 8.2100≤J≤8.2400. For example, the value of the unit cell parameter of the positive electrode material may be 8.2100, 8.2189, 8.2204, 8.2235, 8.2311, 8.2379, 8.2400 or a value within the range consisting of any two of these values. The Dv50 of the positive electrode material is Kμm, 5≤K≤20. For example, the value of K may be 5, 8, 11, 14, 19, 20 or a value within the range consisting of any two of these values. Based on the above embodiments, the present application can further improve the high temperature cycle performance and increase the cycle life by controlling the sphericity, specific surface area, unit cell parameters and Dv50 of the positive electrode material in a coordinated manner within the above range.

[0027] <Method for preparing positive electrode material>

[0028] One embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0029] (1) preparing a precursor containing M1 element and M2 element;

[0030] (2) mixing a precursor containing the M1 element and the M2 element, a lithium source, and a manganese source to obtain a precursor A;

[0031] (3) placing the precursor A in an oxygen-containing atmosphere and performing a first sintering to obtain a first sintered product as the precursor B; or placing the precursor A in an oxygen-containing atmosphere and performing a first sintering to obtain a first sintered product, and then mixing the first sintered product with a precursor containing an element X to obtain the precursor B;

[0032] (4) placing the precursor B in an oxygen-containing atmosphere for a second sintering to obtain a positive electrode material;

[0033] In step (3), the first sintering temperature is 450°C to 650°C, and the time is 4 hours to 8 hours; in step (4), the second sintering temperature is 700°C to 900°C, and the time is 8 hours to 12 hours. The lithium source is lithium carbonate and / or lithium hydroxide, and the manganese source is manganese dioxide and / or manganese tetraoxide. Based on the above embodiments, the positive electrode material prepared by the preparation method of the embodiment of the present application can further improve the high-temperature cycle performance and increase the cycle life.

[0034] The oxygen-containing atmosphere in this application can be an air atmosphere or an oxygen atmosphere.

[0035] <Positive electrode>

[0036] One embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector; the positive electrode material layer comprises the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned method.

[0037] In some embodiments, the positive electrode material layer further includes a ternary lithium material and lithium iron manganese phosphate. For example, the ternary lithium material can be selected from NCM111, NCM523, NCM622, NCM811, NCA, or NCMA. Based on the above embodiments, by mixing and doping the positive electrode material described in this application with the ternary lithium material and lithium iron manganese phosphate material, the energy storage device assembled from the mixed positive electrode material electrode sheet has good high-temperature cycle performance and cycle life, while also improving low-temperature performance and safety performance.

[0038] In some of the embodiments, based on the total mass of the metal elements other than lithium in the positive electrode material layer, the mass percentage of the M1 element is P%, and the mass percentage of the M2 element is Q%, 0.1≤P≤0.5, 0.1≤Q≤0.5. For example, the value of P can be 0.1, 0.2, 0.3, 0.4, 0.5 or a value within the range composed of any two of these values. The value of Q can be 0.1, 0.2, 0.3, 0.4, 0.5 or a value within the range composed of any two of these values. Based on the above embodiments, the present application regulates the ratio of lithium manganese oxide material to ternary lithium material and lithium manganese iron phosphate material in the positive electrode material within a suitable range, so that it can better play a synergistic role, further improve high-temperature cycle performance, increase cycle life, and take into account the improvement of low-temperature performance and safety performance.

[0039] In some embodiments, the positive electrode material layer further includes a positive electrode conductive material. The type of positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; and graphene. These positive electrode conductive materials can be used alone or in any combination.

[0040] In some embodiments, the positive electrode material layer includes a positive electrode binder. The type of the positive electrode binder is not particularly limited. In the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders include, but are not limited to, one or more of the following: resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber-like polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; thermoplastic elastomer-like polymers such as styrene-butadiene-styrene block copolymers or their hydrogenates, ethylene-propylene-diene terpolymers, styrene-ethylene-butadiene-ethylene copolymers, and styrene-isoprene-styrene block copolymers or their hydrogenates; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorinated polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; and polymer compositions having alkali metal ion conductivity. These positive electrode binders may be used alone or in any combination.

[0041] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it can dissolve or disperse the positive electrode active material, conductive material, positive electrode binder, and, if necessary, thickener. Examples of solvents used to form the positive electrode slurry include aqueous solvents and organic solvents. Examples of aqueous media include, but are not limited to, mixed media of alcohol and water, or water. Examples of organic media include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; and aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide.

[0042] Thickeners are typically used to adjust the viscosity of the slurry. When using an aqueous medium, the slurry can be formed using a thickener and a styrene-butadiene rubber emulsion. The type of thickener is not particularly limited, and examples include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. These thickeners may be used alone or in any combination.

[0043] The type of positive electrode current collector is not particularly limited and can be any known material suitable for use as a positive electrode current collector. Examples of positive electrode current collectors include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum; and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0044] To reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.

[0045] non-aqueous electrolyte

[0046] The non-aqueous electrolyte used in the electrochemical device according to the embodiment of the present application includes a lithium salt and a non-aqueous solvent.

[0047] The present application does not particularly limit the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), or lithium difluorooxalatoborate (LiDFOB). Based on the mass of the electrolyte, the mass percentage of the lithium salt may be 8% to 15%, for example, the mass percentage of the lithium salt may be 8%, 9%, 10%, 11%, 12.5%, 13%, 15%, or a range consisting of any two of these values.

[0048] The present application does not particularly limit the type of the above-mentioned non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or cyclic carbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate or methylethyl carbonate. The above-mentioned cyclic carbonate compounds may include but are not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate or vinylethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone. The ether compound may include, but is not limited to, at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. The other organic solvent may include, but is not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate.

[0049] negative electrode

[0050] The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer comprises a negative electrode active material. In some embodiments, the charge capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent unintentional deposition of lithium metal on the negative electrode during charging.

[0051] The negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO x (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.

[0052] The negative electrode material layer of the present application also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the electrolyte or the solvent used in the manufacture of the electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0053] The negative electrode material layer of the present application also includes a conductive agent. The present application does not particularly limit the type of negative electrode conductive agent, as long as it can achieve the objectives of the present application. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots, or graphene. The carbon nanotubes can include, but are not limited to, at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0054] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate coated with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on both surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0055] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.

[0056] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, and it can be at least one of the above-mentioned conductive agent and the above-mentioned binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved. For example, the thickness of the conductive layer is 1μm to 10μm.

[0057] diaphragm

[0058] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode. The diaphragm is used to separate the positive electrode plate and the negative electrode plate to prevent internal short circuit of the secondary battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.

[0059] The present application does not particularly limit the separator, as long as it can achieve the purpose of the present application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid; the separator type may include at least one of woven membranes, non-woven membranes, microporous membranes, composite membranes, rolled membranes, or spun membranes.

[0060] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic material. For example, the inorganic layer includes inorganic particles and a binder. The present application has no particular restrictions on the above-mentioned inorganic particles, and for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, and for example, it may be at least one of the aforementioned binders. The polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0061] The pore size of the separator in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.

[0062] The present application further provides an electronic device comprising a secondary battery according to an embodiment of the present application. The electronic device includes, but is not limited to, a laptop computer, a pen-type computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, a power tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0063] Example

[0064] The following examples and comparative examples, using lithium-ion batteries as an example, provide a more detailed description of the secondary battery embodiments of this application. The preparation methods described herein are merely illustrative; any other suitable preparation methods are within the scope of this application. Furthermore, unless otherwise specified, "parts" and "%" are by mass.

[0065] Example 1-1

[0066] <Preparation of lithium-ion batteries>

[0067] (1) Preparation of positive electrode:

[0068] <Preparation of positive electrode active material>

[0069] (1) adding a manganese sulfate solution and a solution containing vanadium and lanthanum to a reactor, wherein the molar ratio of vanadium to manganese is 0.01 to 0.025, and the molar ratio of lanthanum to manganese is 0.01 to 0.025; maintaining a certain stirring rate in the reactor, performing precipitation reaction and oxidation reaction, and when the particle size Dmin of the coprecipitate is measured to be ≥ 200 nm, a precursor I is obtained; continuing to add manganese sulfate solution and a solution containing vanadium and lanthanum to the precursor I, wherein the molar ratio of vanadium to manganese is The method comprises the following steps: the first step is to prepare a precursor II containing vanadium and lanthanum, wherein the molar ratio of lanthanum to manganese is 0.0005 to 0.01, the molar ratio of lanthanum to manganese is 0.0005 to 0.01, and the reactor continues to maintain a certain stirring rate to carry out precipitation reaction and oxidation reaction. When the co-precipitate particle size Dmin is measured to be ≥300 nm, a precursor II is obtained; the precursor II suspension is transferred to an aging kettle for aging; the aged precursor II suspension is dehydrated, washed, and dehydrated again by a plate and frame filter press or a centrifuge, and then dried to obtain a precursor III containing vanadium and lanthanum.

[0070] (2) mixing a precursor III containing vanadium and lanthanum elements, lithium hydroxide, and manganese dioxide to obtain a precursor A;

[0071] (3) placing the precursor A in an oxygen-containing atmosphere for a first sintering to obtain a first sintered product, and then mixing the first sintered product with a fluorine-containing precursor to obtain a precursor B;

[0072] (4) Precursor B is placed in an oxygen-containing atmosphere for a second sintering to obtain the positive electrode active material Li 1.055 Mn 1.86 V 0.04 La 0.045 O 3.97 F 0.03 ;

[0073] Wherein, the temperature of the first sintering in step (3) is 500° C. and the time is 5 hours; the temperature of the second sintering in step (4) is 800° C. and the time is 10 hours.

[0074] <Preparation of positive electrode sheet>

[0075] The positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) prepared in the above steps are mixed in a mass ratio of 95:2:3, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm and dried to obtain a positive electrode sheet coated with a positive electrode mixture layer on one side. The above steps are repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode mixture layer on both sides. After cold pressing, cutting, slitting, and drying, a positive electrode sheet with a specification of 74mm×867mm is obtained.

[0076] (2) Preparation of a non-aqueous electrolyte: In a dry argon atmosphere glove box, diethyl carbonate was used as a base solvent, lithium hexafluorophosphate (LiPF6) was dissolved in the base solvent, and vinylene carbonate was added as an additive to obtain an electrolyte. Based on the total mass of the electrolyte, the mass percentage of LiPF6 was 12.5%, the mass percentage of vinylene carbonate was 2%, and the balance was diethyl carbonate.

[0077] (3) Preparation of negative electrode: artificial graphite is used as the negative electrode active material, and the negative electrode active material, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8. Then, deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 45 wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6 μm, and dried to obtain a negative electrode sheet coated with a negative electrode mixture layer on one side. The above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode mixture layer on both sides. After cold pressing, cutting, slitting, and drying, a negative electrode sheet with a specification of 76.6 mm × 875 mm is obtained.

[0078] (4) Preparation of diaphragm: A porous polyethylene film with a thickness of 15 μm was used as the diaphragm.

[0079] (5) Preparation of lithium-ion batteries: The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets to act as an insulator. The tabs are welded and wound to obtain a bare cell. The bare cell is placed in a packaging bag, injected with electrolyte, and packaged. A lithium-ion battery is obtained through a process including formation, degassing, trimming, and capacity testing.

[0080] <Test Method>

[0081] (1) High temperature cycle performance test

[0082] Place the lithium-ion battery in a 60°C constant temperature test chamber and let it rest for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it at a constant current of 0.5C to the lithium depletion potential P, then charge it at a constant voltage to a current of 0.05C. Let it rest for 5 minutes, and then discharge it at a constant current of 0.5C to 3.0V. Record this as the initial discharge capacity C0. Repeat this step for 100 cycles, and record the discharge capacity C1 after 100 cycles to calculate the lithium-ion battery cycle capacity retention rate.

[0083] High temperature cycle capacity retention rate = C1 / C0×100%.

[0084] (2) Low temperature discharge performance test:

[0085] Place the lithium-ion battery in a high and low temperature box, adjust the temperature to 25°C, and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. The lithium-ion battery that has reached a constant temperature is discharged to 3.0V at a constant current of 0.5C, and then charged to 4.5V at a constant current of 0.5C, and then charged to a current of 0.05C at the 4.5V voltage constant voltage. Also at a temperature of 25°C, discharge to 3.0V at a constant current of 0.5C, and record the discharge capacity as the initial discharge capacity. At a temperature of 25°C, charge to 4.5V at a constant current of 0.5C, and then charge to a current of 0.05C at the 4.5V voltage constant voltage. Afterwards, place the lithium-ion battery at a temperature of 0°C and let it stand for 30 minutes to keep the temperature of the lithium-ion battery consistent with the external temperature. At 0°C, discharge to 3.0V at a constant current of 0.5C, and record the discharge capacity as the low-temperature discharge capacity.

[0086] Low-temperature discharge capacity retention rate=(low-temperature discharge capacity / initial discharge capacity)×100%.

[0087] (3) Thermal safety performance test:

[0088] Place the lithium-ion battery in a constant temperature environment at 25°C and let it rest for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it at a constant current of 0.5C to the delithiation potential P, then charge it at a constant voltage to a current of 0.05C. Transfer the lithium-ion battery to a hot box and increase the temperature at 5°C / min to 130°C. Maintain the temperature for 60 minutes. The battery passes the thermal safety test if it does not catch fire or explode. Test 20 lithium-ion battery samples in parallel and calculate the pass rate of the thermal safety test.

[0089] Thermal safety pass rate = number of samples passing the test / total number of samples × %.

[0090] (4) Depth distribution test of molar concentration of positive electrode materials

[0091] Energy dispersive X-ray spectroscopy (EDS) analysis was performed on the cross section of the material particles. The geometric center of the cross section was defined as the center of the nearly spherical secondary particle. The molar amount of each element in region I and region II of the positive electrode material and the molar amount of the positive electrode material were tested respectively. The ratio of the molar amount of each element in different regions to the molar amount of the positive electrode material was calculated to obtain the corresponding values ​​of a, b, c, and d.

[0092] The lithium-ion batteries of the following Examples and Comparative Examples differ from Example 1-1 only in that the types of element M1, element M2, and element X, as well as the ratio of the molar amount of each element in Regions I and II to the molar amount of the positive electrode material, are adjusted according to Table 1. The molar amounts of element M1, element M2, and element X in the positive electrode material are adjusted by varying the amount of raw materials added during the preparation process, and the molar ratio of each element to the positive electrode material is then calculated. The performance test results of the lithium-ion batteries of the Examples and Comparative Examples are shown in Table 1 below.

[0093] Table 1

[0094]

[0095]

[0096] *In the above table, the molar ratio of niobium and tantalum in Examples 1-4 is 1:1; Ia is the ratio of the molar amount of the M1 element in region I of the positive electrode material to the molar amount of the positive electrode material, Ib is the ratio of the molar amount of the M2 element in region I of the positive electrode material to the molar amount of the positive electrode material, Ic is the ratio of the molar amount of the X element in region I of the positive electrode material to the molar amount of the positive electrode material, and the same applies to II-a and II-b; I-(a+b+c) is the sum of a, b, and c in region I of the positive electrode material; d is the ratio of the c value in region I of the positive electrode material to the d value in the positive electrode material.

[0097] As can be seen from Table 1, the lithium-ion battery prepared in the embodiment of the present application, when the molar ratio of each element to the positive electrode material in the I region of the positive electrode material satisfies 0.02≤a≤0.05, 0.02≤b≤0.05, 0.001≤c≤0.04, and the molar ratio of each element to the positive electrode material in the II region of the positive electrode material satisfies 0.001≤a≤0.02, 0.001≤b≤0.02, can improve high temperature cycle performance and improve high temperature cycle capacity retention rate. In particular, when the ratio d of the molar amount of the lithium element in the positive electrode material to the molar amount of the positive electrode material is regulated to meet 1≤d≤1.08, the high temperature cycle performance can be further improved and the high temperature cycle capacity retention rate can be improved. In particular, when the positive electrode material in the I region is regulated to meet at least one of 0.05≤a+b+c≤0.1 and 0.001≤c / d≤0.03, the high temperature cycle performance can be further improved and the high temperature cycle capacity retention rate can be improved.

[0098] The lithium-ion batteries of the following Examples 2-1 to 2-19 differ from those of Example 1-47 only in that the specific surface area, unit cell parameters, and Dv50 of the positive electrode material grains are shown in Table 2.

[0099] Table 2

[0100]

[0101] As shown in Table 2, the lithium-ion battery prepared in the embodiment of the present application has the following characteristics: when the specific surface area I (m 2 When the value of I in (g) satisfies 0.3≤I≤1.0, the high temperature performance of the material can be further improved and the high temperature cycle capacity retention rate can be increased. In particular, when the unit cell parameters of the positive electrode material grains are adjusted When the value of J satisfies 8.2100≤J≤8.2400, the high-temperature performance of the material can be further improved, and the high-temperature cycle capacity retention rate can be increased. In particular, when the value of K in the Dv50 parameter Kμm of the positive electrode material grains is regulated to meet 5≤K≤20, the high-temperature performance of the material can be further improved, and the high-temperature cycle capacity retention rate can be increased.

[0102] The lithium-ion batteries of the following Examples 3-1 to 3-12 differ from those of Example 2-18 only in that the P value and Q value are adjusted according to Table 2. The P value and Q value are adjusted by adjusting the addition ratio of each material in the positive electrode material.

[0103] Table 3

[0104]

[0105] As can be seen from Table 3, the lithium-ion battery prepared in the embodiment of the present application, when the positive electrode material also includes a ternary lithium material, lithium manganese iron phosphate or lithium iron phosphate material, the mass percentage content P% of the M1 element satisfies 0.1≤P≤0.5, and the mass percentage content Q% of the M2 element satisfies 0.1≤Q≤0.5. The value of Q can be improved, the high-temperature cycle performance can be improved, the high-temperature cycle capacity retention rate can be improved, and the low-temperature performance and safety performance can be improved, and the low-temperature discharge capacity retention rate and the thermal safety pass rate can be improved.

[0106] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes M1 element, M2 element and X element; The M1 element includes one or more of vanadium, niobium or tantalum, and the ratio of the molar amount of the M1 element to the molar amount of the positive electrode material is a; The M2 element includes one or more of lanthanum, cerium, praseodymium, samarium, dysprosium, ytterbium, yttrium or lutetium, and the ratio of the molar amount of the M2 element to the molar amount of the positive electrode material is b; The X element includes one or more of fluorine, chlorine, sulfur, nitrogen or boron, and the ratio of the molar amount of the X element to the molar amount of the positive electrode material is c; The positive electrode material is a nearly spherical secondary particle, wherein the area of ​​the secondary particle from the outer surface along the radial direction to a depth of 100 nm is region I, and the area from the center of the sphere along the radial direction to a depth of 100 nm is region II; In the I region, 0.02≤a≤0.05, 0.02≤b≤0.05, 0.001≤c≤0.04; In the II region, 0.001≤a≤0.02, 0.001≤b≤0.

02.

2. The positive electrode material according to claim 1, characterized in that In the I region, 0.025≤a≤0.045, 0.025≤b≤0.045, 0.005≤c≤0.03; and / or, In the II region, 0.005≤a≤0.01, 0.005≤b≤0.

01.

3. The positive electrode material according to claim 2, characterized in that The positive electrode material includes lithium element, and the ratio of the molar amount of the lithium element to the molar amount of the positive electrode material is d, 1≤d≤1.

08.

4. The positive electrode material according to claim 3, characterized in that The positive electrode material in the I region satisfies at least one of the following conditions: (1) 0.05≤a+b+c≤0.1; (2)0.001≤c / d≤0.

03.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that: The X element is selected from fluorine and / or boron.

6. The positive electrode material according to any one of claims 1 to 4, characterized in that: The specific surface area of ​​the positive electrode material is Im 2 / g, 0.3≤I≤1.0; and / or, The unit cell parameters of the positive electrode material are 8.2100 ≤ J ≤ 8.2400; and / or, The Dv50 of the positive electrode material is Kμm, 5≤K≤20.

7. The method for preparing the positive electrode material according to any one of claims 1 to 6, characterized in that: The steps include: (1) preparing a precursor containing M1 element and M2 element; (2) mixing a precursor containing the M1 element and the M2 element, a lithium source and a manganese source to obtain a precursor A; (3) placing the precursor A in an oxygen-containing atmosphere for a first sintering to obtain a first sintered product as the precursor B; or placing the precursor A in an oxygen-containing atmosphere for a first sintering to obtain a first sintered product, and then mixing the first sintered product with a precursor containing the element X to obtain the precursor B; (4) placing the precursor B in an oxygen-containing atmosphere for a second sintering to obtain the positive electrode material; Wherein, in step (3), the temperature of the first sintering is 450°C to 650°C, and the time is 4h to 8h; in step (4), the temperature of the second sintering is 700°C to 900°C, and the time is 8h to 12h.

8. A positive electrode sheet, characterized in that: comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector; The positive electrode material layer comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material prepared by the preparation method according to claim 7.

9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode material layer also includes ternary lithium material and / or lithium manganese iron phosphate.

10. The positive electrode sheet according to claim 9, characterized in that: Based on the total mass of metal elements except lithium in the positive electrode material layer, the mass percentage of the M1 element is P%, the mass percentage of the M2 element is Q%, 0.1≤P≤0.5, 0.1≤Q≤0.

5.

11. A secondary battery, characterized in that: The positive electrode sheet comprises the positive electrode sheet as described in any one of claims 8 to 10.

12. An electronic device, characterized in that: The secondary battery according to claim 11 is included.

Citation Information

Patent Citations

  • Positive electrode active material and preparation method thereof, pole piece, energy storage device and power utilization device

    CN116646518A

  • Electrochemical device and electronic device

    CN116802823A

  • Positive electrode active material, positive electrode sheet, secondary battery, battery module, battery pack, and electric device

    CN116802846A

  • Positive electrode material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery

    JP2004327212A

Cited By

  • Positive electrode material and preparation method therefor, positive electrode sheet, secondary battery and electronic device

    WO2026086386A1